Development of a protease-resistant ADAMTS13 to improve stability against proteolytic degradation - Veronica DeYoung; Rex Huang; Hasam Madarati; Rida Malik; Peter Andrisani; Cherie Teney; Colin A. Kretz (Blood Advances)
Abstract: Recombinant ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) was recently approved by the US Food and Drug Administration for the treatment of heritable thrombotic thrombocytopenic purpura, and preclinical studies have demonstrated its efficacy in treating other thrombotic conditions. However, the current ADAMTS13 product is susceptible to degradation by proteases, which may reduce its therapeutic efficacy. Protease-sensitive sites were mapped to the linker regions in ADAMTS13. The linkers were mutated to generate T4L/T8L-ADAMTS13, and an additional elastase cleavage site was also disrupted (T4L/T8L-ADAMTS13[I380G]). Degradation of each ADAMTS13 mutant was tested using purified coagulation or neutrophil proteases, activated neutrophils, or with plasma-based assays. FRETS-VWF73 and microfluidic flow assays were used to characterize their activity. Thrombin, factor Xa, factor XIa, kallikrein, and plasmin cleaved wild-type (WT)-ADAMTS13 at 2 sites. Mutation of both the T4- and T8-linkers protects against degradation at these sites over 3 hours. T4L/T8L-ADAMTS13(I380G) was resistant to elastase degradation. T4L/T8L-ADAMTS13 is stable in plasma thrombin generation assays and fibrinolysis assays, and T4L/T8L-ADAMTS13(I380G) exhibits improved stability to activated neutrophils. T4L/T8L-ADAMTS13 exhibited similar activity to WT-ADAMTS13 using FRETS-VWF73 and in a microfluidic VWF-platelet string cleavage assay. This work identifies prominent protease cleavage sites within ADAMTS13 and demonstrates that disruption of these sites does not impair its capacity to regulate VWF. Future work will explore the therapeutic efficacy of protease-resistant ADAMTS13 in vivo.